Elimination of graft-versus-host disease by in-vitro depletion of alloreactive lymphocytes with a monoclonal rat anti-human lymphocyte antibody (CAMPATH-1). - Waldmann, H; Polliak, A; Hale, G; Or, R; Cividalli, G; Weiss, L; Weshler, Z; Samuel, S; Manor, D; Brautbar, C (1984)
A new monoclonal rat anti-human lymphocyte antibody (CAMPATH-1) which lyses cells with autologous human complement was used for depletion of T lymphocytes from human bone-marrow allografts in vitro before transplantation in 11 high-risk patients. HLA-matched siblings were used as marrow donors. T-cell depletion was substantial when measured by E-rosette formation (0-0.18% residual T cells) and immunofluorescence with a monoclonal anti-T-cell antibody (0-0.5%). No anti-graft-versus-host disease prophylaxis was given after transplantation. Rapid engraftment was reported in all patients, and the post-transplantation course was uneventful. No signs of graft-versus-host disease developed in any of the patients, who were observed for a maximum period of 12 months. The method might be suitable for larger-scale studies in high-risk patients. The late graft failure seen in 2 patients may reflect residual host resistance uncompromised by GvHD.